Computer programming for clinicians: five steps to your new favourite skill. Part 2 - Chow, Ji-Jian (Heart (British Cardiac Society), 2020)
In this article we discuss the learning process and consolidating a useful portfolio of skills for clinical projects: steps 3–5 of 5. Step 4: get social Using the most popular platforms in programming has an advantage: every time you come across an ‘unsolvable’ problem or persistent error message, someone else is likely to have had the same problem and already solved it. Much like learning a foreign language, you will be able to write your first simple program (like writing a sentence) in the first few hours and will become fluent with practice.